Investigation Report and Analysis Knowledge, attitudes and vaccination status regarding HPV vaccines among female healthcare workers at vaccination clinics in Beijing city: a survey report - Haikun QIAN; Wenyan JI; Luodan SUO (Zhongguo gonggong weisheng)
ObjectiveTo understand the knowledge level, attitudes, and vaccination behaviors regarding Human papillomavirus (HPV) vaccines among female healthcare workers providing HPV vaccination services in Beijing′s immunization clinics, and to provide references for improving HPV vaccination rates in Beijing. MethodsIn June 2023, a self-designed online questionnaire was distributed through work groups to female healthcare workers involved in HPV vaccination services at all Beijing immunization clinics providing HPV vaccines. A cross-sectional survey was conducted to assess their HPV vaccine-related knowledge, attitudes, and vaccination status. Chi-square tests and logistic regression were used to analyze factors associated with HPV vaccination behavior. ResultsA total of 1 902 valid questionnaires were collected, representing 17.24% (1 902/11 030) of immunization clinic staff in Beijing, with an HPV vaccination rate of 70.77%. Respondents came from immunization clinics actually providing HPV vaccination services, with a clinic coverage rate of 64.09% (496/774). The median HPV knowledge composite score was 9 (IQR = 8 – 10). 1 520 respondents (79.92%) held positive attitudes toward HPV vaccination. Binary logistic regression analysis showed that the main factors affecting HPV vaccination were: attitude composite score (OR = 2.430; 95%CI = 1.873 – 3.153), perception of high vaccine price (OR = 0.616, 95%CI: 0.427 – 0.888), age (compared to ≥ 50 years, OR values for < 30, 30 – 39, and 40 – 49 years were 33.110, 17.047, and 13.141, respectively), and years of work experience (compared to < 5 years, OR values for 5 – 9, 10 – 14, and ≥ 15 years were 1.639, 2.063, and 1.498, respectively). ConclusionsFemale healthcare workers providing HPV vaccination services in Beijing′s immunization clinics demonstrated good general knowledge of HPV, positive attitudes, and relatively high vaccination rates, providing strong support for HPV vaccination work in Beijing. Vaccination rates can be effectively improved through continued professional training and education of vaccination service personnel citywide and reducing vaccine prices.